The Poland-United States Security Relations in the light of Asymmetry Theory - Kupiecki, Robert (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2016)
Asymmetry in inter-state relations occurs when one of the partners enjoys more freedom of action, resulting from a unique confluence of power factors, thus obtaining a dominant position. Still, in the process, the superior power incurs costs and risks ineffectiveness, thus having to precisely calculate its modus operandi, while the weaker state has at its disposal means to mitigate the consequences of existing power discrepancies. Asymmetry defines Polish-US relations, manifesting itself with full strength in the field of security and defense, given the discrepancies in the two countries’ potentials, different roles played in international relations and the position of the USA as the guarantor of Poland’s security. This article touches upon the effects and the dy¬namics of this situation, perceived as a process that is the result of certain adjustments rather than coercion. Included in it is the ability of influencing the politics of the stronger partner as well as the overvaluation of its results by the weaker side, along with the neglect of the weaker player’s interests by the dominating side. Managing this kind of relations demands maturity and loyalty on both sides. Also, necessary is the institutionalization of deconflicting the priorities of cooperation, using international law tools and consultation mechanisms offered by multilateral forums as well as negotiating mutual relations protecting from their dissolution. Not without importance are also societal sentiments, as well as respect towards all symbolism that underlines mutual relations. Key for Polish-American cooperation, in the field of security, is an understanding of the USA’s global perspective, in which Europe is only one of its dimensions.

Asymetria w stosunkach międzypaństwowych pojawia się, gdy jeden z partnerów dysponuje większą swobodą działania, wynikającą z nagromadzonych czynników potęgi. We wzajemnych interakcjach, strona dominująca ponosi jednak koszty oraz ryzykuje brak efektywności, stąd musi dobrze skalkulować swój sposób działania. Słabszy partner dysponuje bowiem sposobami zarządzania skutkami nierównowagi potencjałów. Asymetria definiuje stosunki polsko-amerykańskie w dziedzinie bezpieczeństwa, zważywszy różnicę potencjałów, ról w stosunkach międzynarodowych oraz pozycję USA jako gwaranta bezpieczeństwa Polski. Niniejszy artykuł podejmuje zagadnienie skutków i dynamiki tej sytuacji, jako procesu będącego raczej efektem dostosowań, aniżeli przymusu. Obecna jest w nim zarówno możliwość wpływania na politykę silniejszego part¬nera oraz nadwartościowanie jej skutków przez stronę słabszą, jak również lekceważenie interesów słabszego przez stronę dominującą. Zarządzanie takimi stosunkami wymaga dojrzałości i lojalności po obu stronach. Konieczna jest także instytucjonalizacja mechanizmów dekonfliktowania priorytetów współpracy, wykorzystanie narzędzi prawa międzynarodowego i mechanizmów konsultacyjnych oferowanych przez fora wielostronne oraz swoistego negocjowania wzajemnych relacji chroniącego przed ich rozpadem. Niebagatelne znaczenie odgrywają też emocje społeczne, jak również respekt dla symboliki podkreślającej wzajemne związki. Kluczowe dla polsko-amerykańskiej współpracy w dziedzinie bezpieczeństwa jest zrozumienie globalnej perspektywy USA, dla której Europa stanowi zaledwie jeden z wymiarów jej strategii.
Teoria asymetrii a stosunki Polska-USA w dziedzinie bezpieczeństwa
Keywords: asymmetry; asymmetry theory; Poland; United States; Security; NATO; International relations; asymetria; teoria asymetrii; Polska; Stany Zjednoczone; bezpieczeństwo; NATO; stosunki międzynarodowe